KESELAMATAN DAN KESEHATAN KERJA (K3): PILAR UTAMA DALAM PRODUKTIVITAS DAN KEBERLANJUTAN - Farras, Farras; Jumhana, Enjum; Fadilah, Anis; Adha, Adha; Novrio, Muhammad Jiddan Anugrah; Haki, Ubay (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
Occupational Safety and Health (OSH) is a vital component in creating a safe, healthy, and productive work environment while protecting workers from the risks of accidents and work- related illnesses. This article provides an in-depth review of the basic concepts of OSH, the underlying regulations, workplace risk factors, and effective implementation strategies. In Indonesia, OSH implementation is governed by Law No. 13 of 2003 on Manpower and Law No. 1 of 1970 on Occupational Safety. Despite the availability of regulations, OSH implementation still faces various challenges, particularly in the informal sector and small and medium enterprises. This article identifies various risk factors that can affect the safety and health of workers, including physical, chemical, biological, ergonomic, and psychosocial risks. Strategies such as strong policy formulation, continuous training, routine audits, and active worker participation can help minimize these risks. The use of modern technology, such as automated detection devices and safety sensors, also supports more effective risk management. The findings of this study reveal that optimal OSH implementation not only reduces workplace accidents and work-related illnesses but also provides significant benefits for companies. These benefits include increased productivity, operational efficiency, worker motivation, and the organization’s reputation as an entity that cares about employee welfare. Therefore, OSH is not merely a legal obligation but also a strategic investment that supports business sustainability and long-term worker welfare